Attaining Selected Sustainable Development Goals in Guatemala : Spending, Provision, and Financing Needs - Perez Ruiz, Esther; Soto, Mauricio (Washington, D.C. : International Monetary Fund, 2019)
Raising living standards continues to be the main challenge facing Guatemala, as a matter of economic success and social cohesion. This paper discusses the spending, financing, and delivery capacity aspects of a viable development strategy for Guatemala couched within the United Nations Sustainable Development Goals (SDGs) agenda. Overall, Guatemala faces additional spending of about 8 1\2 percent of GDP in 2030 to attain health, education, and roads, water, and sanitation infrastructure SDGs. While substantial, these cost estimates are commensurate with a well-defined financing strategy encompassing continuing tax administration efforts, broad-based tax reform, scaled-up private sector participation, and greater spending efficiency. Improving delivery capacities is also essential to secure access of those public goods to all Guatemalans, irrespective of their place of residence, ethnic group, or ability to pay.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet